Biomaterials targeting the microenvironment for spinal cord injury repair: progression and perspectives - Gao, Yating; Wang, Yu; Wu, Yaqi; Liu, Shengwen (Frontiers in Cellular Neuroscience, 2024)
Spinal cord injury (SCI) disrupts nerve pathways and affects sensory, motor, and autonomic function. There is currently no effective treatment for SCI. SCI occurs within three temporal periods: acute, subacute, and chronic. In each period there are different alterations in the cells, inflammatory factors, and signaling pathways within the spinal cord. Many biomaterials have been investigated in the treatment of SCI, including hydrogels and fiber scaffolds, and some progress has been made in the treatment of SCI using multiple materials. However, there are limitations when using individual biomaterials in SCI treatment, and these limitations can be significantly improved by combining treatments with stem cells. In order to better understand SCI and to investigate new strategies for its treatment, several combination therapies that include materials combined with cells, drugs, cytokines, etc. are summarized in the current review.